A comparison of substrate oxidation during prolonged exercise in men at terrestrial altitude and normobaric normoxia following the coingestion of 13C glucose and 13C fructose. Issue 1 (13th January 2017) - O'Hara, John P.; Woods, David R.; Mellor, Adrian; Boos, Christopher; Gallagher, Liam; Tsakirides, Costas; Arjomandkhah, Nicola C.; Holdsworth, David A.; Cooke, Carlton B.; Morrison, Douglas J.; Preston, Thomas; King, Roderick FGJ
Abstract: This study compared the effects of coingesting glucose and fructose on exogenous and endogenous substrate oxidation during prolonged exercise at altitude and sea level, in men. Seven male British military personnel completed two bouts of cycling at the same relative workload (55% W max ) for 120 min on acute exposure to altitude (3375 m) and at sea level ( 113 m). In each trial, participants ingested 1.2 g·min −1 of glucose (enriched with 13 C glucose) and 0.6 g·min −1 of fructose (enriched with 13 C fructose) directly before and every 15 min during exercise. Indirect calorimetry and isotope ratio mass spectrometry were used to calculate fat oxidation, total and exogenous carbohydrate oxidation, plasma glucose oxidation, and endogenous glucose oxidation derived from liver and muscle glycogen. Total carbohydrate oxidation during the exercise period was lower at altitude (157.7 ± 56.3 g) than sea level (286.5 ± 56.2 g, P = 0.006, ES = 2.28), whereas fat oxidation was higher at altitude (75.5 ± 26.8 g) than sea level (42.5 ± 21.3 g, P = 0.024, ES = 1.23). Peak exogenous carbohydrate oxidation was lower at altitude (1.13 ± 0.2 g·min −1 ) than sea level (1.42 ± 0.16 g·min −1, P = 0.034, ES = 1.33). There were no differences in rates, or absolute and relative contributions of plasma or liver glucose oxidation between conditions during the second hour of exercise. However, absolute and relative contributions of muscle glycogen during the second hour were lower at altitude (29.3 ± 28.9 g, 16.6 ± 15.2%) than sea level (78.7 ± 5.2 g ( P = 0.008, ES = 1.71), 37.7 ± 13.0% ( P = 0.016, ES = 1.45). Acute exposure to altitude reduces the reliance on muscle glycogen and increases fat oxidation during prolonged cycling in men compared with sea level. Abstract : This study compared the effects of coingesting glucose and fructose on exogenous and endogenous substrate oxidation during prolonged cycling (120 min at 55% of maximal workload) at terrestrial altitude and sea level in men. Using indirect calorimetry and isotope ratio mass spectrometry, this study showed that acute exposure to altitude reduces the reliance on muscle glycogen and increases fat oxidation during exercise in men, compared with sea level.